(untitled) (Research, Society and Development, 2026)
Cystic fibrosis is an autosomal recessive, multisystem genetic disease associated with high pharmacotherapeutic complexity. This study aims to evaluate the impact of the introduction of ETI on the pharmacotherapy of children and adolescents with CF treated at a referral hospital in Rio de Janeiro, considering its influence on medication deprescribing, prescription complexity, and the number of hospitalizations. This was an observational, retrospective, before-and-after study conducted at a public referral hospital for cystic fibrosis in Rio de Janeiro, Brazil. Thirteen pediatric patients (≥6 years) with confirmed cystic fibrosis who had been using ETI for at least six months were included. The Medication Regimen Complexity Index (MRCI) was applied to two prescriptions per patient: the last prescription prior to ETI initiation and another issued after six months of treatment. Total MRCI scores and Sections A, B, and C were analyzed using paired comparisons with the Wilcoxon test. The mean age was 11 years, with a predominance of females (69.2%). Median MRCI scores were 34.0 points both before and after ETI initiation. An increase in MRCI was observed in 69.2% of patients, while 30.8% showed a reduction. The main variation occurred in Section C, related to additional instructions for use, with statistical significance. Patients with comorbidities presented higher baseline MRCI and less variation after ETI. In the short term, ETI was not associated with reduced pharmacotherapy complexity, highlighting the need for longer follow-up and larger samples.